Behaviour of hybrid timber beam-to-tubular steel column moment connections. (15th January 2017) - Karagiannis, V.; Málaga-Chuquitaype, C.; Elghazouli, A.Y.
Highlights: Experimental study on two types of timber beam-to-tubular steel column connections. Use of reinforcement to prevent wood splitting and increase moment capacity. Investigation of bolt-group point of rotation by means of digital image correlation. Detailed non-linear FE models developed and validated. Incorporation of foundation model approach for modelling embedment in wood. Simplified component-based models applied and verified. Abstract: This paper presents an experimental and numerical study into the response of bolted connections between Glulam timber beams and tubular steel columns. Six specimens involving two different connection types subjected to monotonically increasing bending action are examined. The first connection type incorporates top and seat angles blind-bolted to the column and jointed to the beam through long bolts. The second connection type is formed by a steel T-stub slotted into the timber beam and connected to it by means of transverse bolts. In addition, two reinforcing techniques aimed at enhancing the response of the slotted-in T-stub configuration are investigated. These include the provision of a bottom wedge angle between the beam and the column as well as the use of perpendicular-to-grain screws to delay wood splitting. The experimental set-up, connection configurations and material properties are introduced followed by a detailed account of the test results and observations. The main behavioural patterns are identified from the experiments and key response characteristics such as stiffness, capacity and failure mechanism are discussed. This paper shows that the use of bottom wedge angles leads to significant enhancement in the flexural yield strength of the T-stub connections, accompanied by a relatively small change in the location of the bolt-group point of rotation (monitored herein by means of Digital Image Correlation techniques). Besides, the use of reinforcing screws is shown to be an effective detail for substantially increasing the rotational ductility of the connections. Finite element simulations of the tests are also presented, together with a detailed description of the modelling approaches employed, in order to gain further insight into the behaviour of the connections. Finally, the applicability of simplified component-based expressions, which are suitable for practical design assessment procedures, for the estimation of the stiffness and capacity of the proposed hybrid glulam-to-tubular column connections are presented and discussed.